Non-verbal auditory cognition in patients with temporal epilepsy before and after anterior temporal lobectomy - Bidet-Caulet, Aurélie; Ye, Xiao Lai; Bouchet, Patrick; Guénot, Marc; Fischer, Catherine; Bertrand, Olivier (Frontiers in Human Neuroscience, 2009)
For patients with pharmaco-resistant temporal epilepsy, unilateral anterior temporal lobectomy (ATL) - i.e. the surgical resection of the hippocampus, the amygdala, the temporal pole and the most anterior part of the temporal gyri - is an efficient treatment. There is growing evidence that anterior regions of the temporal lobe are involved in the integration and short-term memorization of object-related sound properties. However, non-verbal auditory processing in patients with temporal lobe epilepsy (TLE) has raised little attention. To assess non-verbal auditory cognition in patients with temporal epilepsy both before and after unilateral ATL, we developed a set of non-verbal auditory tests, including environmental sounds. We could evaluate auditory semantic identification, acoustic and object-related short-term memory, and sound extraction from a sound mixture. The performances of 26 TLE patients before and/or after ATL were compared to those of 18 healthy subjects. Patients before and after ATL were found to present with similar deficits in pitch retention, and in identification and short-term memorisation of environmental sounds, whereas not being impaired in basic acoustic processing compared to healthy subjects. It is most likely that the deficits observed before and after ATL are related to epileptic neuropathological processes. Therefore, in patients with drug-resistant TLE, ATL seems to significantly improve seizure control without producing additional auditory deficits.